Parathyroid hormone-related peptide: a key factor in cell adhesion - Anderson, Jennifer Anne (2006)
Over-expression of parathyroid hormone-related protein (PTHrP) is commonly described in a number of different forms of cancer and it has been suggested that this over-expression leads to tissue-specific metastasis whereby primary tumours have a propensity to metastasise to one particular organ e.g. breast tumours metastasise to bone whereas gastrointestinal tumours favour the liver. The aim of my PhD was to examine the role PTHrP plays in cancer cell adhesion to the extracellular matrix (ECM), to explore a mechanism of action and to elucidate any tissue-specific differences to explain the apparent partiality during metastasis.